Up-Converting Nanocrystals Modified With Fluorescent Markers for the Detection of Amino Acids: Preparation, Characterization, and Sensing Performance - Fei, YuLang; Wu, Kun; Liu, Liang (Frontiers in Chemistry, 2022)
The present work was devoted to developing rhodamine-like chemosensing systems for cysteine (Cys) optical recognition. Aiming at low background light and minimal photobleaching effect, up-converting nanocrystals were firstly synthesized and latterly coated by α-cyclodextrin, and finally used as an exciting host. An energy transfer procedure from these nanocrystals and rhodamine sensors was established via their spectroscopic analysis and emissive decay dynamics comparison. The binding dynamics of our chemosensors for Cys were revealed to have uncomplicated recognition with a stoichiometric ratio of 1 vs. 1. The addition of cysteine increased the emission intensity of the chemosensors. As a consequence, the luminescence off-on effect with sensing selectivity and linear sensing behavior for Cys was demonstrated. Sulfur modification on our chemosensors was shown to be effective in improving their selectivity and photostability.